Distribution of Cardiac and Renal Corin and Proprotein Convertase Subtilisin/Kexin-6 in the Experimental Model of Cardio-Renal Syndrome of Various Severities - Khoury, Emad E.; Fokra, Ahmad; Kinaneh, Safa; Knaney, Yara; Aronson, Doron; Abassi, Zaid (Frontiers in Physiology, 2021)
Congestive heart failure (CHF) often leads to progressive cardiac hypertrophy and salt/water retention. However, its pathogenesis remains largely unclarified. Corin, a cardiac serine protease, is responsible for converting proANP and proBNP to biologically active peptides. Although the involvement of corin in cardiac hypertrophy and heart failure was extensively studied, the alterations in corin and PCSK6, a key enzyme in the conversion of procorin to corin, has not been studied simultaneously in the cardiac and renal tissues in cardio-renal syndrome (CRS). Thus, this study aims at examining the status of PCSK6/corin in the cardiac and renal tissues of rats with CHF induced by the creation of aorto-caval fistula (ACF). We divided rats with ACF into 2 subgroups based on the pattern of their daily sodium excretion, compensated and decompensated. Placement of ACF led to cardiac hypertrophy, pulmonary congestion, and renal dysfunction, which were more profound in the decompensated subgroup. Corin immunoreactive peptide were detected in all heart chambers at myocyte membranal and cytosolic localization and in renal tissue, especially in the apical membrane proximal tubule, mTAL and collecting duct. Interestingly, the expression and abundance of corin in both the cardiac ventricles and renal tissues was significantly increased in compensated animals as compared with the decompensated state. Noteworthy, the abundance of PCSK6 in these tissues followed similar pattern as corin. In contrast, furin expression was upregulated in the cardiac and renal tissues in correlation with CHF severity. We hypothesize that the obtained upregulation of cardiac and renal PCSK6/corin in rats with compensated CHF may represent a compensatory response aiming at maintaining normal Na+ balance, whereas the decline in these two enzymes may contribute to the pathogenesis of avid sodium retention, cardiac hypertrophy, and blunted ANP/BNP actions in decompensated CHF.